Performance enhancement by brain stimulation - Gazerani, P. (Journal of Sports Science & Medicine, 2017)
Number of substances and strategies are available to increase performance in sport (Catlin and Murray, 1996). Since 2004, the World Anti-Doping Agency (WADA) posts an updated list of substances and methods prohibited to athletes. Drugs (e.g., steroids, stimulants) are a major part of this list; however, technologies and methods (e.g., gene doping) are increasingly being identified and added (WADA, 2017). Among technologies and methods that might exert a potential effect on athletic performance, brain stimulation has recently been subjected to extensive discussion. Neuro-enhancement for doping purposes has been termed "neurodoping" in the literature (Davis, 2013); however, this concept needs further documentation before the term "neurodoping" can be used properly.